Edukasi Pemberian MPASI Melalui Optimalisasi Buku KIA Dalam Upaya Pencegahan Stunting Pada Ibu Dengan Anak Usia 6-24 Bulan - Kartika Kartika; Adhin Al Kasanah; Heru Widianto (Pusat Riset dan Inovasi Nasional, 2023)
The problem of stunting is influenced by the low knowledge of mothers in the application of proper complementary feeding. In an effort to fulfill proper MPASI, it is necessary to increase knowledge through information that is easily understood by mothers who have toddlers. Increasing knowledge can be done by optimizing the MCH handbook in applying understanding of the information about MPASI in the MCH handbook and carrying out early detection through reading the height/age chart to detect whether toddlers are stunted or not. The purpose of doing community service in Sayutan Village, Magetan Regency is to increase the knowledge of mothers and toddlers through education on giving MPASI through optimizing the MCH book. The method used in this service is to prepare by conducting a survey of the knowledge possessed by toddler mothers about giving MPASI. The next stage is the implementation of activities, namely education with counseling about the information on complementary feeding contained in the MCH handbook and how to interpret PB/U charts to detect stunting. The final stage of this activity is to evaluate the implementation of activities by measuring the level of knowledge before education is carried out and after evaluation is carried out. The results of this community service show that there is an increase in the level of good knowledge of 80.5% compared to before education, namely less knowledge of 48.8%. Information in the MCH handbook can be an appropriate reference if it is read and understood correctly. With increased understanding of a mother will further improve the health status of toddlers in the family.